Aplicación de estrategias metodológicas para controlar la agresividad en los niños y niñas de primer año de educación general básica del centro educativo Ing. Jorge Alex Serrano Aguilar, de el canton El Guabo año lectivo 2012-2013 - Rodríguez Tituana, Cristina Jhury (2013)
Education as a foundation for the development of human beings and society itself, aims to develop the skills and potential of the student, as well as create responsible citizens, tolerant with each other and with the community, that’s when the problem arises of these children who reflect their aggressive behavior in the surrounding context, either by different situations in which they are immersed, why the teacher seek the methodological tools needed to counteract these types if behaviors. So the student can access a better quality of life and therefore can be strengthened family ties, since you can control their emotions which help him in his social relations and in the regulation of behavior.